DETERMINAN OPINI AUDIT GOING CONCERN - Nafsiyyah, Zakiyyatun Dea; Prameswari, Desty Villa; Sartika, Eka; Umyana, Ayu (Accounting Department, Politeknik Negeri Bandung, 2023)
Abstract: This study was conducted in order to determine the impact of audit quality, total asset turnover, company size, growth opportunity, DER, DAR, and previous year's audit opinion on audit opinion regarding business continuity in food and beverage subsector companies located on the IDX in the period 2020 to 2022. Financial statements are secondary data used in research with purposive sampling in determining and based on predetermined characteristics there are 78 companies. Quantitative becomes a research model using logistic regression so as to obtain results where previous period Audit Opinions have an impact on Going Concern Audit Opinions, while Audit Quality, Total Asset Turnover, Company Size, Company Growth, Debt To Equity, Debt To Asset have no impact on Going Concern Audit Opinions in food and beverage subsector manufacturing companies. Keywords: Debt To Asset, Debt To Equity, Audit Quality, Going Concern Audit Opinion, Previous Year Audit Opinion, Total Asset Turnover, Company Size